Monitoring biofouling as a management tool for reducing toxic antifouling practices in the Baltic Sea. (15th June 2020) - Wrange, Anna-Lisa; Barboza, Francisco R.; Ferreira, Joao; Eriksson-Wiklund, Ann-Kristin; Ytreberg, Erik; Jonsson, Per R.; Watermann, Burkard; Dahlström, Mia
Abstract: Over two million leisure boats use the coastal areas of the Baltic Sea for recreational purposes. The majority of these boats are painted with toxic antifouling paints that release biocides into the coastal ecosystems and negatively impact non-targeted species. Regulations concerning the use of antifouling paints differ dramatically between countries bordering the Baltic Sea and most of them lack the support of biological data. In the present study, we collected data on biofouling in 17 marinas along the Baltic Sea coast during three consecutive boating seasons (May–October 2014, 2015 and 2016). In this context, we compared different monitoring strategies and developed a fouling index (FI) to characterise marinas according to the recorded biofouling abundance and type (defined according to the hardness and strength of attachment to the substrate). Lower FI values, i.e. softer and/or less abundant biofouling, were consistently observed in marinas in the northern Baltic Sea. The decrease in FI from the south-western to the northern Baltic Sea was partially explained by the concomitant decrease in salinity. Nevertheless, most of the observed changes in biofouling seemed to be determined by local factors and inter-annual variability, which emphasizes the necessity for systematic monitoring of biofouling by end-users and/or authorities for the effective implementation of non-toxic antifouling alternatives in marinas. Based on the obtained results, we discuss how monitoring programs and other related measures can be used to support adaptive management strategies towards more sustainable antifouling practices in the Baltic Sea. Graphical abstract: Image 1 Highlights: Large-scale biofouling patterns in Baltic leisure boat marinas were studied. High spatial-temporal variation of biofouling among marinas was found. Local drivers and inter-annual variation are the main drivers of biofouling patterns. Monitoring can support the transition towards non-toxic antifouling practices.